The effect of higher sludge recycling rate on anaerobic treatment of palm oil mill effluent in a semi-commercial closed digester for renewable energy - Sulaiman, Alawi; Busu, Zainuri; Tabatabaei, Meisam; Yacob, Shahrakbah; Abd. Aziz, Suraini; Hassan, Mohd Ali; Shirai, Yoshihito (Science Publications, 2009)
Problem statement: A 500 m3 semi-commercial closed anaerobic digester was constructed for Palm Oil Mill Effluent (POME) treatment and methane gas capture for renewable energy. During the start-up operation period, the Volatile Fatty Acids (VFA) accumulation could not be controlled and caused instability on the system. Approach: A settling tank was installed and sludge was recycled as to provide a balanced microorganisms population for the treatment of POME and methane gas production. The effect of sludge recycling rate was studied by applying Organic Loading Rates (OLR)(between 1.0 and 10.0 kgCOD m-3 day-1) at different sludge recycling rates (6, 12 and 18 m3 day-1). Results: At sludge recycling rate of 18 m3 day-1, the maximum OLR was 10.0 kgCOD m-3 day-1 with biogas and methane productivity of 1.5 and 0.9 m3 m-3 day-1, respectively. By increasing the sludge recycling rate the VFA concentration was controlled below its inhibitory limit (1000 mg L-1) and the COD removal efficiency recorded was above 95% which indicated good treatment performance for the digester. Two methanogens species (Methanosarcina sp. and Methanosaeta concilii) had been identified from sludge samples obtained from the digester and recycled stream. Conclusion: By increasing the sludge recycling rate upon higher application of OLR, the treatment process was kept stable with high COD removal efficiency. The biogas and methane productivity were initially improved but reduced once OLR and recycling rate were increased to 10.0 kg COD m3 day-1 and 18 m3 day-1 respectively.